ISOLATION OF BACTERIA AS A BIOREMEDIATION AGENT FOR RECLAMATION OF MERCURY-CONTAMINATED SOILS - Muhammad Idris; Rizki Amelia Nasution; Ulfayani Mayasari (Jurnal Bioteknologi dan Biosains Indonesia, 2023)
Gold mining commonly involves the use of mercury, which generates hazardous and toxic mercury-based waste, leading to soil contamination and adverse effects on human health. Bioremediation has been explored as a potential solution to this issue. This study aimed to identify indigenous microbial species with potential as bioremediation agents, assess their ability to influence chemical properties, and evaluate their effectiveness in reducing mercury content. The research was conducted in five stages: isolation of native bacteria, testing the potential of microorganisms, assessing the ability to reduce mercury, conducting soil tests, and identifying bacterial characteristics through microscopic and biochemical analyses. The results revealed three types of indigenous microbes, namely Pseudomonas, Neisseria, and Klebsiella bacteria, with the highest potential as bioremediation agents. These bacterial isolates were found to enhance the availability of phosphorus in the soil, maintain soil pH, but had no effect on total soil nitrogen. Furthermore, the bacterial isolates exhibited the ability to reduce mercury content after treatment with NA isolates.